Developing a Framework to Support the Delivery of Effective Pain Management for Children: An Exploratory Qualitative Study. (28th October 2020) - Simons, Joan; Carter, Bernie; Craske, Jennie
Abstract : Two million children are admitted to hospital every year in the UK and between 59% and 94% will experience pain, with 27–40% of them experiencing moderate to severe pain. Currently, there are a number of well-researched guidelines on children's pain available, yet pain prevalence is high. Despite the guidelines, there is a lack of an overall framework that includes the necessary components to deliver effective pain management. This study was built on previous work about key elements that support children's pain management, by exploring their relevance and practical application with 43 healthcare practitioners. We carried out focus groups with band 5 nurses ( n  = 6) and advanced nurse practitioners ( n  = 11) and semistructured interviews with pain nurses ( n  = 16) and consultants ( n  = 10). We also presented and discussed our findings with an advisory group. Findings demonstrated that the following elements were considered to be important: delivering pain management with confidence, supporting colleagues with protocols and guidance, empowering parents to be involved in pain management, and adopting an individual approach to a child and family. These elements formed the basis of a framework for children's pain management. Some practitioners indicated that pain management required education and more resources, and that the culture of an area could influence pain management practice. The framework brings together elements that have the potential to improve the management of children's pain through its use as an education tool. Each interrelated element of the framework plays an important part in the overall management of children's pain. The need now is to make the dissemination of the findings accessible to health care practitioners, parents, and educators. Next steps include the development of infographic posters, an animation, and a free online course, which will incorporate the use of Bloom's taxonomy.